2013
DOI: 10.1158/1538-7445.am2013-5465
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5465: LY2875358, a bivalent MET antibody with anti-tumor activity through blocking HGF as well as inducing degradation of MET, differentiates from a one-armed 5D5 MET antibody.

Abstract: MET is involved in many mechanisms of cancer proliferation and metastasis. Inappropriate activation of MET can be induced by HGF-independent mechanisms such as gene amplification, specific genetic mutations, and transcriptional up-regulation, or by HGF-dependent autocrine or paracrine mechanisms. LY2875358 is a novel humanized bivalent MET antibody currently in phase I clinical testing (trial NCT01287546). LY2875358 has high neutralization and internalization activities against MET for inhibiting HGF-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…LY2875358 has demonstrated significant antitumor activity in preclinical studies, even against MET mutants that did not respond to onartuzumab [196][197][198]. A phase II study is currently evaluating the combination of LY2875358 with erlotinib as first-line treatment for patients with advanced NSCLC and activating EGFR mutations (NCT01897480).…”
Section: Met/hgf Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…LY2875358 has demonstrated significant antitumor activity in preclinical studies, even against MET mutants that did not respond to onartuzumab [196][197][198]. A phase II study is currently evaluating the combination of LY2875358 with erlotinib as first-line treatment for patients with advanced NSCLC and activating EGFR mutations (NCT01897480).…”
Section: Met/hgf Antibodiesmentioning
confidence: 99%
“…MET Eli Lilly [196][197][198] ABT-700 MET AbbVie [199] ARGX111 MET arGEN-x [200] TAK-701 HGF Takeda Pharmaceutical Co [201] …”
Section: Antibodiesmentioning
confidence: 99%
“…236, 237 In contrast, LY-2875358 is a bivalent MET receptor antibody that can inhibit both HGF-mediated signaling by binding to the MET receptor, as well as HGF-independent activation of the MET pathway by inducing internalization and degradation of MET. 238 LY-2875358 has confirmed antitumor activity in in vivo and in vitro models. 239, 240 A phase I trial as a single agent and in combination with erlotinib has been reported with no dose limiting toxicities, serious or grade III adverse events.…”
Section: Met Positive Nsclcmentioning
confidence: 88%
“…238 LY-2875358 has confirmed antitumor activity in in vivo and in vitro models. 239, 240 A phase I trial as a single agent and in combination with erlotinib has been reported with no dose limiting toxicities, serious or grade III adverse events. 241 Currently, LY-2875358 is being evaluated in 2 phase II trials, including a randomized phase II with erlotinib versus erlotinib alone in patients with advanced-stage EGFR-mutated NSCLC (NCT01897480), as well as a single-agent or combined with erlotinib in patients with MET diagnostic positive NSCLC that has progressed on erlotinib.…”
Section: Met Positive Nsclcmentioning
confidence: 88%
“…Emibetuzumab (LY-2875358, Eli Lilly) is a humanized, bivalent anti-c-Met antibody that inhibits both ligand-dependent and ligand-independent activation of c-Met. 73 In the case of HGF-dependent c-Met activation, emibetuzumab inhibits HGF binding to c-Met, c-Met phosphorylation, and tumor growth both in vitro and in vivo, similar to a humanized, one-armed 5D5 anti-c-Met antibody (precursor of onartuzumab). In the case of HGF-independent c-Met activation by MET gene amplification in tumors, emibetuzumab promotes internalization and degradation of c-Met.…”
Section: Antibody-based Therapeutics Targeting Hgf and C-metmentioning
confidence: 99%